Rasiotekanan darah terhadap tinggi badan dalam diagnosis hipertensi pada remaja - Kristina Ambarita; Oke Rina Ramayani; Munar Lubis; Isti Ilmiati; Rafita Ramayati; Rusdidjas dr (Fakultas Kedokteran USU, 2017)
Diagnosis of hypertension in children and adolescents according to the Fourth Report from the National High Blood Pressure Education Program (NHBPEP) Working Group on Children and Adolescents 2004 is complicated, influenced by gender, age, and height. This resulted in an effort to find alternative ways to overcome the lack of practical diagnostic tool hypertension in adolescents. Current research is centered on the use of anthropometric variables to detect hypertension in adolescents. Height is a factor that plays an important role in determining blood pressure because of body size affects blood pressure. The blood pressure to height ratio is a simple method that can be used for diagnosing hypertension in adolescents. This ratio is not influenced by age which means determining the cut-off point of hypertension is not according to age specific, and the ratio is not adjusted in height so that this ratio can be used in adolescents who are short or tall. This ratio has a high sensitivity and specificity in the diagnosis of hypertension, which is high capabilities in the detection of hypertension and to determine non hypertension in adolescents.Keyword :adolescence, blood pressure to height ratio, diagnosis, hypertension